Analysis of the Impact of Industry 4.0 Technologies on Service Sector - Bayindir, Bisar Jiyan; Shafighi, Najla; Hajibashi, Anahita Amini (Archives of Business Research, 2024)
The Fourth Industrial Revolution, or Industry 4.0, is characterized by a variety of technologies, such as IoT, AI, Big Data Analytics, Robotics, Blockchain, and AR, that cause a major transformation to happen. This research deals with the influence of these technologies on the performance of services within the service sector. In more detail, the research examines the influence of three main considerations: technology adoption, level of skills that employees possess, and amount of investment in technology. Despite the potential for Industry 4.0 technologies to increase the operational efficiency and create more satisfactory customer experiences, technology integration and workforce upskilling prove to be challenging aspects of the change. Using quantitative data analysis and a questionnaire survey, this research helps to analyze the problem and provide the solution through answering the question: how do Industry 4.0 technologies affect the performance of services in the service sector? Major research implications include that Industry 4.0 technologies highly contribute to efficient service performance because of increased efficiency, cost mitigation, and customer satisfaction. In order for those advantages to be reached, nonetheless, they need to be accompanied by significant investment in technology and human capital. The key advantages produced by this research consist in the improved understanding of how to support the strategic management instruments and the analysis concerning the working environment over the long term. An additional point entails that as a result of COVID-19 digital technologies have been adopted faster by all sectors. Therefore, any organization needs to be prepared for digital resilience. As a whole, the conclusion provides recommendations for strategic management support of service sector companies through digital technologies.